The Behavioral Disorder of a Character in Ashmora Paria Novel by Herlinatiens - Nurani Azmi, Dian; Supriyanto, Teguh; Baehaqie, Imam (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
Behavioral disorder refers to behavioral deviation from the applied norms in a social system. One of them is - sexual disorder. For some novelists, they also use sexual disorder in their novels. One of them is Ashmora Paria by Herlinatiens. The main character of the novel commits sexual disorder due to some factors. This research focused on the character’s behavioral disorder in the novel. This research describes the sexual disorder of the character and the causes. The applied approach is literature psychology with psychoanalysis theory and semiotic method. The applied data analysis techniques were heuristic and hermeneutic reading. The analysis showed that the behavioral disorder of the character in the novel was sexual disorder. The type of sexual disorder was absolute inversion homosexual or sexual-orientation disorder. Characters that had this disorder were Paria, Rie Shiva, Mahendra, and Mahadevi. They suffered from the sexual disorder due to traumas, frustrations, and pleasant homosexual experience